Preventive Care Uptake and Long-Term Healthcare Use Among Children with Fetal Opioid Exposure in Ontario, Canada: A Population-Based Retrospective Cohort Study - Han, Arum; Pratt Tremblay, Gabrielle; Pugliese, Michael; Fell, Deshayne; Corsi, Daniel J (International Journal of Population Data Science, 2026)
Introduction Data on preventive care visits and long-term healthcare use patterns among children with prenatal opioid exposure remain limited. From a life course perspective, early impacts on health care engagement may shape patterns of health service use across childhood. Objective To characterise early and long-term healthcare service visits among children with prenatal opioid exposure using linked population-based health administrative databases from Ontario, Canada. Methods We conducted a population-based retrospective cohort study of live-born infants born between April 1, 2007, and March 31, 2018, who were born to mothers aged 15-50 years and who were eligible for provincial health insurance for at least 3 months before conception. Prenatal opioid use identified during routine prenatal care was extracted from clinical and perinatal health records. The primary outcome was the uptake of well-child visits until 24 months of age, an important early life preventive care period. Rates of all-cause inpatient, outpatient, and emergency department visits were examined and compared across the follow-up period and within specific time intervals up to 13 years of age. Results The final cohort totalled 1,343,653 live births, of whom 13,290 children (0.99%) had documented prenatal exposure to opioids. Prenatal opioid exposure was associated with reduced incidence of well-child visits (adjusted incidence rate ratio: 0.82 (95% CI: 0.81, 0.83)) from birth to 2 years. Exposed children were less likely to receive an enhanced 18-month well-child visit (adjusted risk ratio: 0.89 (95% CI: 0.88, 0.90)). Prenatal exposure was associated with increased rates of emergency department visits, specialist visits, hospitalisations and same-day surgery visits over the follow-up period. Differences in rates of health care visits were most pronounced in early childhood and attenuated for some services at older ages. Conclusions Prenatal opioid exposure was associated with reduced uptake of preventive health services and greater use of ambulatory care. This finding is consistent with a life course model, in which early gaps in preventive care may influence later-life care use patterns, and highlights the need for effective strategies to promote access to and engagement with preventive care services for opioid-exposed children.